Low Survivals and Rapid Demographic Decline of a Threatened Estuarine Delphinid - Lin, Wenzhi; Zheng, Ruiqiang; Liu, Binshuai; Chen, Shenglan; Lin, Mingli; Liu, Mingming; Liu, Wenhua; Li, Songhai (Frontiers in Marine Science, 2022)
Beibu Gulf’s (BBG) Indo-Pacific humpback dolphins present both a genetic differentiation and phenotypical differences from conspecifics from other areas of the South China Sea. Given the recent urbanization and industrialization in southern China, humpback dolphins from the BBG warrant conservation attention. However, this population’s demographic trend is unclear, making it hard to take conservation measures. To assess the population status of humpback dolphins in the BBG, photo-identification surveys were conducted between 2015 and 2019 in the inshore region surrounding the Dafeng River Estuary, which represents the most urbanized and industrialized coastal area of the BBG region. Robust design modeling suggested a constant survival for the female adults (0.89, 95% CI: 0.83–0.94). In comparison, the survival of the juvenile and sex-undetermined adults dropped from 0.92 (95% CI: 0.75–0.98) in 2015 to 0.86 (95% CI: 0.71–0.94) in 2016 and bounced back to 0.89 (95% CI: 0.80–0.94) in 2018. The low level of survival may justify the rapid decline in the annual population size from 156 (95% CI: 133–184) in 2015 to 102 (95% CI: 98–107) in 2019. We found little impact of emigration on the dolphin demographic process. Instead, the low and fluctuating survivals, although with overlapping confidence intervals, seemingly suggested a presence of strong marine stressor(s). Our study highlighted that obtaining high-resolution data is essential to improving our understanding of the demographic dynamics. Moreover, the anthropogenic stress in the BBG region should be quantitatively studied in both temporal and spatial perspectives, to help depict the ecological response of the dolphins to anthropogenic activities.